PENGEMBANGAN BAHAN AJAR MEMBACA PERMULAAN BERBASIS TEKNOLOGI MARI MEMBACA UNTUK SISWA KELAS RENDAH DI MASA PANDEMI COVID-19 - Aprilia, Bunga Delia; Djuanda, Dadan; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2021)
This study was carried out by the findings of researcher, where there was the second grade students at Bojong Koneng Elementary School who didn’t have the early reading skills. From the results of the initial observations conducted by researchers, this problem happens due to the use of teaching materials that are still conventional during the implementation of online learning, especially in the Covid-19 pandemic period. The purpose of this study was to obtain a solution to the problems that occurred at Bojong Koneng Elementary School. The researcher chose to develop technology-based early reading teaching materials as a solution. The research instrument used in this study is the guidelines interviews, expert validation sheets, and documentation. The final result obtained by the researcher, based on the validation of the develop technology-based early reading teaching materials has a very valid feasibility rate.